Intranasal P Particle Vaccine Provided Partial Cross-Variant Protection against Human GII.4 Norovirus Diarrhea in Gnotobiotic Pigs - Kocher, Jacob (American Society for Microbiology, 2014)
Noroviruses (NoVs) are the leading cause of nonbacterial acute gastroenteritis worldwide in people of all ages. The P particle is a novel vaccine candidate derived from the protruding (P) domain of the NoV VP1 capsid protein. This study utilized the neonatal gnotobiotic pig model to evaluate the protective efficacies of primary infection, P particles, and virus-like particles (VLPs) against NoV infection and disease and the T cell responses to these treatments. Pigs either were vaccinated intranasally with GII.4/1997 NoV (VA387)-derived P particles or VLPs or were inoculated orally with a GII.4/2006b NoV variant. At postinoculation day (PID) 28, pigs either were euthanized or were challenged with the GII.4/2006b variant and monitored for diarrhea and virus shedding for 7 days. The T cell responses in intestinal and systemic lymphoid tissues were examined. Primary NoV infection provided 83% homologous protection against diarrhea and 49% homologous protection against virus shedding, while the P particle and VLP vaccines provided cross-variant protection (47% and 60%, respectively) against diarrhea. The protection rates against diarrhea are significantly inversely correlated with T cell expansion in the duodenum and are positively correlated with T cell expansion in the ileum and spleen. The P particle vaccine primed for stronger immune responses than VLPs, including significantly higher numbers of activated CD4(+) T cells in all tissues, gamma interferon-producing (IFN-γ(+)) CD8(+) T cells in the duodenum, regulatory T cells (Tregs) in the blood, and transforming growth factor β (TGF-β)-producing CD4(+) CD25(−) FoxP3(+) Tregs in the spleen postchallenge, indicating that P particles are more immunogenic than VLPs at the same dose. In conclusion, the P particle vaccine is a promising vaccine candidate worthy of further development. IMPORTANCE The norovirus (NoV) P particle is a vaccine candidate derived from the protruding (P) domain of the NoV VP1 capsid protein. P particles can be easily produced in Escherichia coli at high yields and thus may be more economically viable than the virus-like particle (VLP) vaccine. This study demonstrated, for the first time, the cross-variant protection (46.7%) of the intranasal P particle vaccine against human NoV diarrhea and revealed in detail the intestinal and systemic T cell responses by using the gnotobiotic pig model. The cross-variant protective efficacy of the P particle vaccine was comparable to that of the VLP vaccine in pigs (60%) and to the homologous protective efficacy of the VLP vaccine in humans (47%). NoV is now the leading cause of pediatric dehydrating diarrhea, responsible for approximately 1 million hospital visits for U.S. children and 218,000 deaths in developing countries. The P particle vaccine holds promise for reducing the disease burden and mortality.